Innovations In Non-Invasive Liver Disease Diagnostics (E.G., Fatty Liver, Cirrhosis) - Nafees, Samraiz; Anas, Muhammad; Ali Ayub, Muhammad Umer; Sharma, Tanay Anilkumar; Vayolipoyil, Sarath; Bangash, Sudhair Abbas (Journal of Neonatal Surgery, 2025)
Background: Fatty liver disease (FLD) and cirrhosis are some of the major diseases of the liver and a major cause of morbidity. Liver biopsy, despite being a useful method of diagnosing the disease, is an invasive technique, expensive, and accompanied by risk and pain. Non-invasive diagnostic methods that are under development today, like FibroScan, Shear Wave Elastography (SWE), Magnetic Resonance Elastography (MRE), and diagnostics with the use of biomarkers, are good options. Nonetheless, they are not evenly adopted among different stakeholders and are assumed to be successful. Objective: Due to this purpose, this research study will determine the level of awareness, images, and usage of non-invasive technologies for liver disease diagnosis among medical workers, investigators, and patients. It also explores the correlation between the major determinant measures, which include trust in technology, perceived effectiveness, cost concern, and availability. Methods: A Quantitative cross-sectional survey consisting of 250 respondents spread across five provinces of Pakistan was used. Data on demographic factors, awareness, perceived effectiveness, practicing behaviour, and factors were obtained with the help of a structured questionnaire. Some of the statistical analyses used included normality testing, reliability testing (Cronbach’s Alpha), construct validity through Principal component analysis (PCA), Pearson correlation, and multiple linear regression. Results: The findings according to the data indicated non-normality in the data of age and normality in the data of years of experience. The internal consistency was good, and Cronbach's Alpha was 0.871, which demonstrated good reliability of the survey instrument. PCA advocated construct validity, which had a cumulative variance above 70 percent. Pearson's correlation revealed a positive correlation among all the important variables. The predictors of adoption of diagnostic tools were found to be cost concern, trust in technology, and awareness by multiple regression analysis. The positive relationship. between R and adopting behaviour was 61.4 percent (R 2 = 0.614). Conclusion: Liver diseases are being tested in terms of non-invasive diagnoses and have begun to achieve popularity. The widespread spread of innovations is highly dependent on aspects that include cost, accessibility, trust in the technology, and awareness. They can be largely improved by offering better training, reducing the cost of implementation, and exposure to technology. The paper presents utilitarian knowledge in healthcare policy formulation, clinical decision making, and diagnostic innovation research..